Acceptability and preferences of psychological interventions for attention and executive problems in young university students - Vickie Plourde; Sylvie Gaudet; Mylène Ross-Plourde; Maryse Lord (Cogent Psychology)
Intervention acceptability is considered as one of the factors related to the efficacy and favourable outcomes post-therapy. Prospective or anticipated acceptability, which is measured before undertaking therapy, has yet to be assessed in the context of psychotherapies targeting emerging adults. This research aimed at measuring the anticipated acceptability and preference toward cognitive behavioral therapy (CBT) and mindfulness-based therapy (MBT) (Study 1), and three delivery formats (in-person, online, or blended; Study 2). University students aged 18–25 (Study 1: N = 21; Study 2: N = 102) read vignettes for each intervention and filled questionnaires online. In Study 1, there were higher levels of acceptability toward CBT than MBT. In Study 2, acceptability levels were significantly higher for the in-person, followed by blended and online formats. There was also a significantly higher acceptability for in-person CBT compared to MBT. The in-person format was also preferred, but preferences for CBT or MBT were similar. Overall, students indicate a higher acceptability for CBT (Study 1) and CBT in-person (Study 2). As preferences toward both interventions were similar, asking about these could help personalizing our approach with university students.